2010
DOI: 10.1371/journal.pone.0011266
|View full text |Cite
|
Sign up to set email alerts
|

Depression, Antidepressant Use and Mortality in Later Life: The Health in Men Study

Abstract: ContextDepression is associated with increased mortality, but it is unclear if this relationship is dose-dependent and if it can be modified by treatment with antidepressants.ObjectiveTo determine if (1) the association between depression and mortality is independent of other common potential causes of death in later life, (2) there is a dose-response relationship between increasing severity of depression and mortality rates, and (3) the use of antidepressant drugs reduces mortality rates.MethodsCohort study o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
62
1
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(71 citation statements)
references
References 59 publications
(52 reference statements)
6
62
1
2
Order By: Relevance
“…This result confirms previous research where depression was shown to be a risk factor for several chronic conditions (Lépine & Briley, 2011;Centers for Disease Control and Prevention, 2012;Janszky et al, 2007;Clarke & Currie, 2009;Frasure-Smith & Lesperance, 2006;Katon et al, 2007;Almeida, Alfonso, Hankey, & Flicker, 2010;Moussavi et al, 2007;Pratt et al, 1996), and chronic disease, conversely, was shown to be a risk factor for depression (Janszky et al, 2007;Clarke & Currie, 2009;Frasure-Smith & Lesperance, 2006;Katon et al, 2007;Holden et al, 2013;Strine et al, 2008). A large longitudinal study has shown that depression is associated with future health-compromising behaviors (Walsh, Senn, & Carey, 2013), which helps explain increased risk for several chronic conditions that are lifestylerelated.…”
Section: Frequencysupporting
confidence: 91%
“…This result confirms previous research where depression was shown to be a risk factor for several chronic conditions (Lépine & Briley, 2011;Centers for Disease Control and Prevention, 2012;Janszky et al, 2007;Clarke & Currie, 2009;Frasure-Smith & Lesperance, 2006;Katon et al, 2007;Almeida, Alfonso, Hankey, & Flicker, 2010;Moussavi et al, 2007;Pratt et al, 1996), and chronic disease, conversely, was shown to be a risk factor for depression (Janszky et al, 2007;Clarke & Currie, 2009;Frasure-Smith & Lesperance, 2006;Katon et al, 2007;Holden et al, 2013;Strine et al, 2008). A large longitudinal study has shown that depression is associated with future health-compromising behaviors (Walsh, Senn, & Carey, 2013), which helps explain increased risk for several chronic conditions that are lifestylerelated.…”
Section: Frequencysupporting
confidence: 91%
“…One factor contributing to the widespread use of ADs is that they are considered both effective and relatively safe, with mild or rare side effects that are preferred over the debilitating effects of untreated depression. Depression is widely considered a disorder that causes needless suffering [5], and it is associated with an elevated risk of mortality [6,7,8]. People with depression are more likely to suffer from many comorbid physical disorders, such as cardiovascular disease [8,9,10], and they are at elevated risk for suicide [11].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, while each AD probably has a distinct symptom profile, there is good reason to suspect that they all degrade the functioning of some adaptive processes in the body [3]. Consistent with this hypothesis, several cohort studies of community samples have associated AD use with an elevated risk of cardiovascular events and death, even after controlling for depressive symptoms and other comorbidities [6,7,57]. Although cohort studies cannot conclusively demonstrate causation, randomized controlled trials are often underpowered due to the rarity of death events and the limited duration of follow-up.…”
Section: Introductionmentioning
confidence: 99%
“…Of the six studies included in the “general population” category, the increased HR was significantly driven by the study by Coupland et al [2], which consisted of patients aged 65–100, hardly being representative of what most would consider the “general population.” The studies by Ryan et al [4] and Almeida et al [5] were also of older adults and Smoller et al [6] exclusively followed postmenopausal women. The only two studies that had samples which would typically be considered the “general population” both failed to show a significant increase in mortality with AD use [7, 8].…”
mentioning
confidence: 99%